2015
DOI: 10.1001/jamaophthalmol.2014.5312
|View full text |Cite
|
Sign up to set email alerts
|

A 50% vs 30% Dose of Verteporfin (Photodynamic Therapy) for Acute Central Serous Chorioretinopathy

Abstract: IMPORTANCE A randomized clinical trial is needed to evaluate what is the best photodynamic therapy (PDT) protocol to use for acute central serous chorioretinopathy.OBJECTIVE To compare the efficacy and safety of a 50% dose of verteporfin (a method of PDT) with the efficacy and safety of a 30% dose for acute central serous chorioretinopathy. DESIGN, SETTING, AND PARTICIPANTSA multicenter, noninferiority, double-masked, randomized, controlled, clinical trial in which 131 patients (131 eyes) with acute central s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 43 publications
1
54
0
2
Order By: Relevance
“…Eight studies reported that outcome assessors were masked to treatment group and we judged them at low risk of detection bias (Bae 2011; Browning 1993; Chan 2008; Dang 2013; Ratanasukon 2012; Roisman 2013; Sawa 2014; Zhao 2015). Eight studies did not report any masking and the treatments were different and so we judged them at high risk of detection bias (Boscia 2008; Coskun 2014; Kim 2013; Klatt 2011; Leaver 1979; Lim 2010; Rahbani-Nobar 2011; Semeraro 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported that outcome assessors were masked to treatment group and we judged them at low risk of detection bias (Bae 2011; Browning 1993; Chan 2008; Dang 2013; Ratanasukon 2012; Roisman 2013; Sawa 2014; Zhao 2015). Eight studies did not report any masking and the treatments were different and so we judged them at high risk of detection bias (Boscia 2008; Coskun 2014; Kim 2013; Klatt 2011; Leaver 1979; Lim 2010; Rahbani-Nobar 2011; Semeraro 2012).…”
Section: Resultsmentioning
confidence: 99%
“…144 A recent randomized clinical trial compared two doses of Visudyne in CSC. 145 This noninferiority trial attempted to demonstrate that 30% dose would be as effective as the 50% dose. However, noninferiority was not achieved and it found that the 50% dose of Visudyne is superior to 30% dose.…”
Section: Liposome and Lipid-based Nanomedicinementioning
confidence: 99%
“…In a randomized clinical trial recruiting 131 patients, Zhao et al [53] compared the efficacy and safety of a 50% dose of PDT with the efficacy and safety of a 30% dose for acute CSC. During the 1-year follow-up, half-dose PDT was superior to 30% dose PDT in terms of resolution of subretinal fluid, fluorescein angiography leakage, recurrence of NSD and fluorescein leakage.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Many aspects remain to be determined, including the effects of PDT on chorioretinal atrophy, the role of PDT for patients showing no or minimal choroidal hyperpermeability, the action of PDT on the rate of recurrences and the cumulative effect of repeated treatments [52,53,54,55,56,57]. …”
Section: Treatment Optionsmentioning
confidence: 99%